Effect of Training & Development, Organizational Learning on Employee Competence - Teti Susilowati; Muryanto Agus Nuswantoro; Emy Susiatin; Evi Evi (PT ARRUS Intelektual Indonesia, 2022)
This study aims to analyze the effect of training and development, organizational learning on the competence of employees at the University of Semarang. The population in this study were employees of the University of Semarang, especially education and support staff. Samples were taken as many as 73 employees. The sampling technique used is probability sampling technique. The data processing method uses SPSS 26. The results of the analysis show that training and organizational learning development have an effect on the competence of Semarang University employees. Training and Development, Organizational Learning is able to explain the variations that occur in the Employee Competence variable by 44.6% while the rest is explained by other causes outside this model.